Catalyst system for olefin polymerization and application thereof
By using a catalyst system in olefin polymerization, including catalyst A, catalyst B and cocatalyst, the problems of processing difficulties and low strength caused by excessive crystallization of hyperbranched polyethylene are solved, and a balance between strength and toughness of the polymer is achieved.
Patent Information
- Application Number
- CN202311408767.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-10-27
AI Technical Summary
Hyperbranched polyethylene has difficulties in processing and forming and low strength due to low crystallization.
A catalyst system for olefin polymerization is provided, including a mixed product of catalyst A and catalyst B, and a cocatalyst, which can maintain ethylene polymerization activity at higher temperatures and balance the strength and toughness of the polymer.
Catalyzed ethylene polymerization at high temperatures is achieved, and the obtained polymer has higher tensile strength while maintaining a higher elongation of break, solving the balance problem between strength and toughness.
Smart Images

Figure BDA0004517449830000011 
Figure BDA0004517449830000012 
Figure BDA0004517449830000021
Abstract
Description
Technical Field
[0001] The present application relates to the field of olefin polymerization, and in particular to a catalyst system for olefin polymerization and its application. Prior art
[0002] Polyolefins are the most productive and widely used polymer materials among synthetic resins. They are characterized by high cost performance, good mechanical properties, excellent processing properties, stable chemical properties, good electrical insulation properties and recyclability. They are widely used in agriculture, industry, medical care and daily life. Ethylene is the simplest and cheapest olefin monomer. The synthesis of polyolefin products with different structures and properties starting from ethylene or using ethylene as the main monomer is one of the hot topics in the field of polymer synthesis research.
[0003] In 1995, Brookhart et al. found that the α-diimine palladium and nickel catalysts of the following formula (1) can catalyze the homopolymerization of ethylene to obtain hyperbranched polyethylene with rich branched structures (J. Am. Chem. Soc., 1995, 117 (23): 6414-6415).
[0004]
[0005] In 1998, Grubbs et al. found that the salicylaldehyde imine type nickel catalyst of the following formula (2) can also catalyze the homopolymerization of ethylene to obtain polyethylene with a branched structure (Organometallics. 1998, 17: 3149-3151).
[0006]
[0007] This type of polyethylene has good solubility, low solution and melt viscosity, and good toughness. It can be used as a rubber material or polyolefin elastomer and has good application prospects in the fields of automotive parts, seals, photovoltaic films, etc. However, this type of polyethylene also has bottleneck problems that need to be solved urgently, such as extremely low crystallinity and amorphous polyethylene, which makes processing and molding difficult and the product strength is insufficient, which brings certain difficulties to the promotion and application of this type of material. In order to solve the above problems, some researchers have designed a special catalyst structure to increase the molecular weight of the polymer and reduce the degree of branching to improve its strength, but this method is bound to weaken the original good toughness and elasticity of hyperbranched polyethylene.
[0008] Chinese patent CN110590980A designed and synthesized an α-diimine nickel catalyst with a large steric skeleton, which changed the electronic and spatial effects around the metal center of the catalyst, thereby achieving the goal of obtaining a high molecular weight, low branching polymer at a high temperature. However, the ligand structure of this catalyst is relatively complex, the synthesis process is cumbersome, and the preparation cost is high, which is not conducive to industrial application. Summary of the invention
[0009] The purpose of the present application is to provide a catalyst system for olefin polymerization and a method for catalyzing olefin polymerization using the same, wherein the catalyst system can achieve high ethylene polymerization activity at high temperatures and achieve a balance between rigidity and toughness of the polyethylene obtained by polymerization, thereby solving the problems of difficult processing and molding and low strength of hyperbranched polyethylene due to low crystallinity.
[0010] In order to achieve the above object, on the one hand, the present application provides a catalyst system for olefin polymerization (also referred to as a catalyst composition herein), comprising a mixed product of the following components:
[0011] (1) Catalyst A, at least one selected from the group consisting of metal complexes represented by general formula (I) or general formula (II):
[0012]
[0013] In formula (I), R' is a C1-C8 straight or branched alkylene group, a C13-C21 diaryl alkylene group, a C2-C8 dialkylsilylene group or a C12-C20 diarylsilylene group; and Each independently represents an unsubstituted or substituted cyclopentadienyl, fluorenyl or indenyl; M is a Group IVB metal; each X is independently selected from halogen, C1-C6 alkyl or C2-C6 alkenyl,
[0014]
[0015] In formula (II), and Each independently represents a cyclopentadienyl, fluorenyl or indenyl group, R" and R"' are independently selected from hydrogen, C1-C8 straight chain or branched alkyl; M is a Group IVB metal; each X is independently selected from halogen, C1-C6 alkyl or C2-C6 alkenyl;
[0016] (2) Catalyst B is at least one selected from the group consisting of metal complexes represented by general formula (IIIa) or (IIIb):
[0017]
[0018] In formula (IIIa) and (IIIb), R1 and R2 are independently hydrogen, C1-C4 alkyl, C1-C4 haloalkyl, halogen or C1-C4 alkoxy; R3, R4, R6 and R7 are independently C1-C6 alkyl, C3-C6 cycloalkyl, unsubstituted or substituted phenyl or phenyl-substituted C1-C4 alkyl; R5 and R8 are independently hydrogen, C1-C6 alkyl, C3-C6 cycloalkyl, unsubstituted or substituted phenyl, phenyl-substituted C1-C4 alkyl, halogen or C1-C4 alkoxy; M is nickel or palladium; X is halogen, wherein the substituted phenyl has 1 to 5 substituents selected from the group consisting of halogen, C1-C4 alkyl and C1-C4 haloalkyl, and
[0019] (3) A co-catalyst selected from one or more of alkyl aluminum, alkyl aluminoxane and alkyl aluminum halide.
[0020] On the other hand, the present application provides a method for olefin polymerization, comprising contacting ethylene monomer, and optionally C3-C10 α-olefin, with the catalyst system of the present application in an organic solvent to carry out a polymerization reaction.
[0021] The catalyst system provided in the present application can catalyze the polymerization of ethylene monomer in an organic solvent at a relatively high temperature (≥60°C). Compared with the prior art, the polymer prepared in the present application has a higher tensile strength while maintaining a relatively high elongation at break, achieving a balance between strength and toughness. Moreover, the olefin polymerization method provided in the present application is simple and easy to operate, does not require a complex catalyst structure and harsh reaction conditions, and is easy to realize industrial production. DETAILED DESCRIPTION
[0022] The specific implementation methods of the present application are described in detail below, but it should be noted that the protection scope of the present application is not limited by these specific implementation methods, but is determined by the claims in the appendix.
[0023] Any specific numerical value disclosed herein (including the endpoint of the numerical range) is not limited to the exact value of the numerical value, but should be understood to also cover values close to the exact value, such as all possible numerical values within the range of ±5% of the exact value. In addition, for the disclosed numerical range, the endpoint values of the range, the endpoint values and the specific point values in the range, and the specific point values can be arbitrarily combined to obtain one or more new numerical ranges, and these new numerical ranges should also be regarded as specifically disclosed herein.
[0024] Unless otherwise specified, the terms used herein have the same meaning as commonly understood by those skilled in the art. If a term is defined herein and its definition is different from the commonly understood meaning in the art, the definition herein shall prevail.
[0025] In the context of this application, unless otherwise expressly defined or the meaning is beyond the comprehension of a person skilled in the art, hydrocarbon or hydrocarbon derivative groups having more than 3 carbon atoms (such as propyl, propoxy, butyl, butane, butene, butenyl, hexane, etc.) have the same meaning when not preceded by the prefix "n". For example, propyl is generally understood to be n-propyl, and butyl is generally understood to be n-butyl, unless otherwise expressly defined.
[0026] In the context of this application, the term "mixed product" refers to the product obtained after the components of the catalyst system are contacted and mixed. Depending on the physicochemical properties and interactions of the components, the product may contain a physical mixture and / or a chemical reaction product of the components.
[0027] In this application, except for the contents clearly stated, any matters or items not mentioned are directly applicable to the aspects known in the art without any changes. Moreover, any embodiment described herein can be freely combined with one or more other embodiments described herein, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of this application, and should not be regarded as new contents not disclosed or anticipated herein, unless a person skilled in the art considers that the combination is obviously unreasonable.
[0028] All patent and non-patent literature, including but not limited to textbooks and journal articles, mentioned herein are incorporated herein by reference in their entirety.
[0029] In a first aspect, the present application provides a catalyst system for olefin polymerization, the catalyst system comprising a mixed product of the following components:
[0030] (1) Catalyst A, at least one selected from the group consisting of metal complexes represented by general formula (I) or general formula (II):
[0031]
[0032] In formula (I), R' is a C1-C8 straight or branched alkylene group, a C13-C21 diaryl alkylene group, a C2-C8 dialkylsilylene group or a C12-C20 diaryl silylene group, preferably a C1-C4 straight or branched alkylene group, a C13-C17 diaryl alkylene group, a C2-C4 dialkylsilylene group or a C12-C16 diaryl silylene group, more preferably a methylene group, an ethylene group, an isopropylidene group, a diphenylmethylene group, a dimethylsilylene group or a diphenylsilylene group; and Each independently represents an unsubstituted or substituted cyclopentadienyl, fluorenyl or indenyl; M is a Group IVB metal; each X is independently selected from halogen, C1-C6 alkyl or C2-C6 alkenyl,
[0033]
[0034] In formula (II), and Each independently represents a cyclopentadienyl, fluorenyl or indenyl group, R" and R"' are each independently selected from hydrogen, C1-C8 straight chain or branched alkyl, preferably hydrogen, C1-C4 straight chain or branched alkyl; M is a Group IVB metal; each X is independently selected from halogen, C1-C6 alkyl or C2-C6 alkenyl;
[0035] (2) Catalyst B is at least one selected from the group consisting of metal complexes represented by general formula (IIIa) or (IIIb):
[0036]
[0037] In formula (IIIa) and (IIIb), R1 and R2 are independently hydrogen, C1-C4 alkyl, C1-C4 haloalkyl, halogen or C1-C4 alkoxy; R3, R4, R6 and R7 are independently C1-C6 chain alkyl, C3-C6 cycloalkyl, unsubstituted or substituted phenyl or phenyl-substituted C1-C4 alkyl; R5 and R8 are independently hydrogen, C1-C6 chain alkyl, C3-C6 cycloalkyl, unsubstituted or substituted phenyl, phenyl-substituted C1-C4 alkyl, halogen or C1-C4 alkoxy; M is nickel or palladium; X is halogen, wherein the substituted phenyl has 1 to 5 substituents selected from the group consisting of halogen, C1-C4 alkyl and C1-C4 haloalkyl, and
[0038] (3) A co-catalyst selected from one or more of alkyl aluminum, alkyl aluminoxane and alkyl aluminum halide.
[0039] In a preferred embodiment, in formula (I) and formula (II), M is titanium, zirconium or hafnium, and X is halogen.
[0040] In the catalyst system of the present application, as the catalyst B, for example, the following metal complexes can be cited as specific examples:
[0041]
[0042] It should be noted that these metal complexes can be used alone or in any proportion.
[0043] In the catalyst system of the present application, the general structural formula of the alkyl aluminum as a co-catalyst can be shown as the following formula (IVa):
[0044] Al(R)3 (IVa)
[0045] Wherein, each group R is independently selected from C1-C8 alkyl, preferably selected from methyl, ethyl, propyl, butyl and isobutyl, most preferably selected from ethyl and isobutyl. In addition, the alkyl aluminum can be used alone or in any combination of any proportion.
[0046] Specifically, examples of the alkyl aluminum include trimethyl aluminum (Al(CH3)3), triethyl aluminum (Al(CH3CH2)3), tri-n-propyl aluminum (Al(n-C3H7)3), tri-isopropyl aluminum (Al(i-C3H7)3), tri-isobutyl aluminum (Al(i-C4H9)3), tri-n-pentyl aluminum (Al(n-C5H 11 )3) Tri-n-hexyl aluminum (Al(n-C6H 13 )3), diethylmethylaluminum (Al(CH3)(CH3CH2)2), and dimethylethylaluminum (Al(CH3)2(CH3CH2)), etc., among which trimethylaluminum, triethylaluminum, and triisobutylaluminum are preferred.
[0047] In the catalyst system of the present application, the general structural formula of the alkylaluminoxane used as a co-catalyst may be as shown in the following formula (IVb) or (IVc):
[0048]
[0049] Wherein, each group R is independently selected from C1-C8 alkyl, preferably selected from methyl, ethyl, propyl, butyl and isobutyl, most preferably selected from methyl and ethyl, and n is any integer in the range of 1-50, preferably any integer in the range of 10-30. In addition, the alkylaluminoxane can be used alone or in combination in any proportion.
[0050] Specifically, the alkylaluminoxane is preferably selected from methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, n-butylaluminoxane, modified methylaluminoxane and modified ethylaluminoxane, and more preferably selected from methylaluminoxane and modified methylaluminoxane.
[0051] In the catalyst system of the present application, the general structural formula of the halogenated alkyl aluminum as a co-catalyst can be shown as follows (IVd):
[0052] Al(R) n X 3-n (IVd)
[0053] Wherein, each group R is independently selected from C1-C8 alkyl, preferably selected from methyl, ethyl, propyl, butyl and isobutyl, most preferably selected from ethyl and isobutyl, X is halogen, preferably chlorine or bromine, and n is 1 or 2. In addition, the alkyl aluminum halide can be used alone or in combination in any proportion.
[0054] Specifically, as the alkyl aluminum halide, for example, there can be mentioned dimethylaluminum monochloride (Al(CH3)2Cl), dimethylaluminum dichloride (Al(CH3)Cl2), diethylaluminum monochloride (Al(CH3CH2)2Cl), diethylaluminum dichloride (Al(CH3CH2)Cl2), dipropylaluminum monochloride (Al(C3H7)2Cl), dipropylaluminum dichloride (Al(C3H7)Cl2)), di-n-butylaluminum monochloride (Al(n-C4H9)2Cl), di-n-butylaluminum dichloride (Al(n-C4H9)Cl2), diisobutylaluminum monochloride (Al(i-C4H9)2Cl), diisobutylaluminum dichloride (Al(i-C4H9)Cl2), di-n-pentylaluminum monochloride (Al(n-C5H 11 )2Cl), dichloropentylaluminum (Al(n-C5H 11 )Cl2), diisopentylaluminum monochloride (Al(i-C5H 11 )2Cl), dichloroisopentylaluminum (Al(i-C5H 11 )Cl2), di-n-hexylaluminum chloride (Al(n-C6H 13 )2Cl), dichlorohexyl aluminum (Al(n-C6H 13 )Cl2), diisohexylaluminum monochloride (Al(i-C6H 13 )2Cl), dichloroisohexylaluminum (Al(i-C6H 13 )Cl2), chloromethyl ethylaluminum (Al(CH3)(CH3CH2)Cl), chloromethyl propylaluminum (Al(CH3)(C3H7)Cl), chloromethyl n-butylaluminum (Al(CH3)(n-C4H9)Cl), chloromethyl isobutylaluminum (Al(CH3)(i-C4H9)Cl), chloroethyl propylaluminum (Al(CH2CH3)(C3H7)Cl), chloroethyl n-butylaluminum (Al(CH2CH3)(n-C4H9)Cl), chloroethyl isobutylaluminum (Al(CH2CH3)(i-C4H9)Cl), etc., preferably selected from diethylaluminum chloride, ethylaluminum dichloride, di-n-butylaluminum chloride, n-butylaluminum dichloride, diisobutylaluminum chloride, di-n-hexylaluminum chloride and n-hexylaluminum dichloride, further preferably selected from diethylaluminum chloride and ethylaluminum dichloride.
[0055] In a preferred embodiment, in the catalyst system of the present application, the molar ratio of the catalyst A to the catalyst B, calculated on the basis of the central metal atom, is 1:10 to 10:1, preferably 2:8 to 8:2, and more preferably 4:6 to 6:4.
[0056] In a preferred embodiment, in the catalyst system of the present application, the molar ratio of the total amount of the co-catalyst, calculated as aluminum atoms, to the total amount of the catalyst A and the catalyst B, calculated as central metal atoms, is (10-5000):1, preferably (100-2000):1, and more preferably (500-1000):1.
[0057] In a second aspect, the present application also provides a method for olefin polymerization, comprising contacting an ethylene monomer, and optionally a C3-C10 α-olefin, with the catalyst system of the present application in an organic solvent to carry out a polymerization reaction.
[0058] In a preferred embodiment, the C3-C10 α-olefin is selected from propylene, 1-butene, 1-hexene, 1-octene, or a combination thereof.
[0059] In a preferred embodiment, the organic solvent is selected from aromatic hydrocarbons, alkanes and halogenated alkanes, preferably selected from one or more of toluene, dichloromethane, n-pentane, cyclopentane, n-hexane, cyclohexane, n-heptane, n-octane and Isopare series solvents, more preferably selected from one or more of n-hexane, cyclohexane and toluene.
[0060] In a preferred embodiment, the polymerization reaction conditions include: a temperature of 0-150° C., preferably 60-100° C.; and a polymerization pressure of 0.1-4.0 MPa, preferably 0.5-3.0 MPa.
[0061] In the olefin polymerization method of the present application, there is no particular limitation on the manner in which the catalyst A, catalyst B and co-catalyst are added to the polymerization reaction system. The co-catalyst may be added first, and then the catalyst A and catalyst B, or the catalyst A and catalyst B may be added first, and then the co-catalyst may be added, or the three may be contacted and mixed first and then added together or separately at the same time, or part of the co-catalyst may be added first, and then the catalyst A, catalyst B and the remaining co-catalyst may be added simultaneously. When the catalyst A, catalyst B and co-catalyst are added separately, they may be added sequentially through the same feeding pipeline, or they may be added simultaneously or sequentially through multiple feeding pipelines.
[0062] In addition, in the olefin polymerization method of the present application, the alkyl aluminum, alkyl aluminoxane or alkyl aluminum halide used as a co-catalyst is generally used in the form of a solution. When preparing the solution of the co-catalyst, there is no particular restriction on the solvent used, as long as it can dissolve the co-catalyst. The solvent is generally selected as an alkane solvent, such as n-pentane, isopentane, cyclopentane, neopentane, etc., or an aromatic solvent, such as toluene, ethylbenzene, xylene, etc. According to the present application, in order to facilitate subsequent separation, it is preferred to use a solvent that is the same as the polymerization solvent; or a solvent that is the same as one of the solvents in the mixed solvent for polymerization.
[0063] Example
[0064] The embodiments of the present application will be described in detail below in conjunction with examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be construed as limiting the scope of the present application.
[0065] The testing method for the molecular weight of the polymer obtained in the following examples and comparative examples is as follows: The polymer molecular weight is measured using a PL-220 gel permeation chromatograph of Polymer Laboratories, using 1,2,4-trichlorobenzene as the mobile phase, polystyrene as the standard sample, a differential detector, a flow rate of 1.0 mL / min, a measuring temperature of 150° C., and a sample concentration of 2.0 mg / mL. The polymer dispersity index (PDI) is calculated based on the measured weight average molecular weight and number average molecular weight.
[0066] The degree of branching of the polymers obtained in the following examples and comparative examples was calculated based on the carbon nuclear magnetic resonance spectrum. The specific method is as follows: the microstructure of the polyethylene sample was determined using a Bruker Avance 600M nuclear magnetic resonance spectrometer. The sample was dissolved in deuterated o-dichlorobenzene to prepare a solution. The test temperature was 120°C. The nuclear magnetic resonance hydrogen spectrum was obtained by scanning 2000 times and 6000 times respectively. 1 H-NMR) and carbon nuclear magnetic resonance spectroscopy ( 13 C-NMR).
[0067] The thermal properties (melting point T m , melting enthalpy ΔH and crystallinity) testing method is: using TA-2000 differential scanning calorimeter (DSC) to measure, using nitrogen atmosphere, heating from 20°C to 150°C at a rate of 20°C / min, staying for 5 minutes to eliminate thermal history, then decreasing to -70°C at a rate of 20°C / min, staying for 5 minutes, and then increasing to 150°C at a rate of 20°C / min, recording the secondary heating curve.
[0068] The tensile properties (tensile strength and breaking strain) of the polymers obtained in the following examples and comparative examples are tested as follows: the standard GB / T1040-1992 is used for determination, the testing instrument is a universal material testing machine - Zwick / Roell-Z020, the spline type is Type I, and the splines are prepared using a micro high-performance composite material molding system of model HAAKE MiniJet II and a Tensile bar ISO527-5A tensile mold (L75mm, W12.5mm, H2mm), the injection molding temperature is 280-300°C, the mold temperature is 80-100°C, the holding pressure is 1150bar, and the holding time is 15s.
[0069] In the following examples and comparative examples:
[0070] The polymerization activity was calculated as follows:
[0071] W=Q / (M×H)
[0072] Wherein, W is the polymerization activity; Q is the yield of the obtained polymer (in g); M is the total molar amount of catalyst A and catalyst B (in mol); H is the polymerization time (in h)
[0073] The relative crystallinity X of the polymer is calculated as follows:
[0074]
[0075] ΔH f is the measured melting enthalpy of polyethylene; The melting enthalpy of 100% crystalline polyethylene is 291.7 J / g.
[0076] Example 1
[0077] In a glove box, catalyst A1 (ethylenebis-1,1-(tetrahydroindenyl) zirconium dichloride) (0.011 mmol), catalyst B1 (0.011 mmol) shown above, dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After the 2L high-pressure polymerization kettle was purged with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and the above-configured catalyst solution were added to the kettle in sequence. When the reactor was heated to 60°C, 1.5MPa ethylene was introduced, and the polymerization reaction was carried out for 30 minutes under stirring at 200rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P1 was weighed. The polymerization activity and polymer test results of this embodiment are shown in Table 1.
[0078]
[0079] Example 2
[0080] In a glove box, catalyst A2 (rac-vinyl bis indenyl zirconium dichloride) (0.011 mmol), catalyst B2 (0.011 mmol) described above, dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and the above-configured catalyst solution were added to the kettle in sequence. When the reactor was heated to 60°C, 2.3 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P2 was weighed. The polymerization activity and polymer test results of this embodiment are shown in Table 1.
[0081]
[0082] Example 3
[0083] In a glove box, catalyst A3 (dimethylsilyl-bis-(1-indenyl) zirconium dichloride) (0.011 mmol), the catalyst B6 described above (0.011 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After a 2L high-pressure polymerization kettle was purged with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and the above-configured catalyst solution were added to the kettle in sequence. When the reactor was heated to 80°C, 1.5MPa ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P3 was weighed. The polymerization activity and polymer test results of this embodiment are shown in Table 1.
[0084]
[0085] Example 4
[0086] In a glove box, catalyst A2 (rac-vinyl bis-indenyl zirconium dichloride) (0.011 mmol), catalyst B2 (0.011 mmol) described above, dichloromethane (10 mL), methylaluminoxane (22 mmol), and ethylaluminum dichloride (6.6 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and the above-configured catalyst solution were added to the kettle in sequence. When the reactor was heated to 60°C, 2.3 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P4 was weighed. The polymerization activity and polymer test results of this embodiment are shown in Table 1.
[0087] Example 5
[0088] In a glove box, catalyst A2 (rac-vinyl bis-indenyl zirconium dichloride) (0.011 mmol), catalyst B2 (0.011 mmol) described above, dichloromethane (10 mL), and modified methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After a 2L high-pressure polymerization kettle was purged with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and the above-configured catalyst solution were added to the kettle in sequence. When the reactor was heated to 60°C, 2.3 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P5 was weighed. The polymerization activity and polymer test results of this embodiment are shown in Table 1.
[0089] Example 6
[0090] In a glove box, catalyst A2 (rac-vinyl bis indenyl zirconium dichloride) (0.0055mmol), catalyst B2 (0.0165mmol) described above, dichloromethane (10mL), and methylaluminoxane (22mmol) were added to a 100mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and the above-configured catalyst solution were added to the kettle in sequence. When the reactor was heated to 60°C, 2.3MPa ethylene was introduced, and the polymerization reaction was carried out for 30min at a speed of 200rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P6 was weighed. The polymerization activity and polymer test results of this embodiment are shown in Table 1.
[0091] Example 7
[0092] In a glove box, catalyst A2 (rac-vinyl bis-indenyl zirconium dichloride) (0.0165mmol), catalyst B2 (0.0055mmol) described above, dichloromethane (10mL), and methylaluminoxane (22mmol) were added to a 100mL conical flask in sequence, mixed and set aside. After a 2L high-pressure polymerization kettle was purged with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and the above-configured catalyst solution were added to the kettle in sequence. When the reactor was heated to 60°C, 2.3MPa ethylene was introduced, and the polymerization reaction was carried out for 30min at a speed of 200rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P7 was weighed. The polymerization activity and polymer test results of this embodiment are shown in Table 1.
[0093] Example 8
[0094] In a glove box, catalyst A2 (rac-vinyl bis indenyl zirconium dichloride) (0.011 mmol), catalyst B2 (0.011 mmol) described above, dichloromethane (10 mL), and methylaluminoxane (11 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After a 2L high-pressure polymerization kettle was purged with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and the above-configured catalyst solution were added to the kettle in sequence. When the reactor was heated to 60°C, 2.3 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P8 was weighed. The polymerization activity and polymer test results of this embodiment are shown in Table 1.
[0095] Example 9
[0096] In a glove box, catalyst A2 (rac-vinyl bis indenyl zirconium dichloride) (0.011 mmol), catalyst B2 (0.011 mmol) described above, dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After a 2L high-pressure polymerization kettle was purged with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and the above-configured catalyst solution were added to the kettle in sequence. When the reactor was heated to 80°C, 2.3 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P9 was weighed. The polymerization activity and polymer test results of this embodiment are shown in Table 1.
[0097] Example 10
[0098] In a glove box, catalyst A2 (rac-vinyl bis-indenyl zirconium dichloride) (0.011 mmol), catalyst B2 (0.011 mmol) described above, dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After a 2L high-pressure polymerization kettle was purged with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and the above-configured catalyst solution were added to the kettle in sequence. When the reactor was heated to 100°C, 2.3 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P10 was weighed. The polymerization activity and polymer test results of this embodiment are shown in Table 1.
[0099] Comparative Example 1
[0100] In a glove box, catalyst A2 (rac-vinyl bis indenyl zirconium dichloride) (0.022mmol), dichloromethane (10mL), and methylaluminoxane (22mmol) were added to a 100mL conical flask in sequence, mixed and set aside. After a 2L high-pressure polymerization kettle was purged with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and the above-configured catalyst solution were added to the kettle in sequence. When the reactor was heated to 100°C, 2.3MPa ethylene was introduced, and the polymerization reaction was carried out for 30 minutes under stirring at 200rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P11 was weighed. The polymerization activity and polymer test results of this comparative example are shown in Table 1.
[0101] Comparative Example 2
[0102] In a glove box, the catalyst B2 (0.022 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) described above were added to a 100 mL conical flask in sequence, mixed, and set aside. After a 2L high-pressure polymerization kettle was purged with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and the above-configured catalyst solution were added to the kettle in sequence. When the reactor was heated to 60°C, 2.3 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P12 was weighed. The polymerization activity and polymer test results of this comparative example are shown in Table 1.
[0103] Comparative Example 3
[0104] In a glove box, metallocene catalyst (dibutylsilyl-bis-(1-indenyl) zirconium dichloride) (0.011 mmol), nickel metal catalyst B' (0.011 mmol) as shown in the following formula V, dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After a 2L high-pressure polymerization kettle was purged with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and the above-configured catalyst solution were added to the kettle in sequence. When the reactor was heated to 60°C, 1.5MPa ethylene was introduced, and the polymerization reaction was carried out for 30 minutes under stirring at 200rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P13 was weighed. The polymerization activity and polymer test results of this comparative example are shown in Table 1.
[0105]
[0106] Table 1 Polymerization test results of various embodiments and comparative examples
[0107]
[0108] From the comparison between the above embodiments and the comparative examples, it can be seen that by using the catalyst system provided in the present application, the molecular weight distribution of the obtained polymer becomes wider, has a certain degree of crystallinity, and has a higher tensile strength while maintaining a higher fracture strain rate, thereby achieving a balance between strength and toughness, giving the polyethylene material a wider application.
[0109] From the comparison between the embodiment and comparative example 3, it can be seen that compared with the existing catalyst system, the catalyst system provided in the present application has higher polymerization activity (greater than 2 times) at a higher polymerization temperature (60°C), and the obtained polyethylene has a higher degree of branching, a lower degree of crystallinity, a larger fracture strain, and better performance in toughness.
[0110] Although the specific implementations of the present application have been described in detail above in conjunction with the embodiments, it should be pointed out that the protection scope of the present application is not limited by these specific implementations, but is determined by the appended claims. Those skilled in the art may make appropriate changes to these implementations without departing from the technical ideas and purposes of the present application, and these changed implementations are obviously also included in the protection scope of the present application.
Claims
1. A catalyst system for olefin polymerization, comprising a mixed product of the following components: (1) Catalyst A, at least one selected from the group consisting of metal complexes represented by general formula (I) or general formula (II): In formula (I), R' is a C1-C8 straight or branched alkylene group, a C13-C21 diaryl alkylene group, a C2-C8 dialkylsilylene group or a C12-C20 diaryl silylene group, preferably a C1-C4 straight or branched alkylene group, a C13-C17 diaryl alkylene group, a C2-C4 dialkylsilylene group or a C12-C16 diaryl silylene group, more preferably a methylene group, an ethylene group, an isopropylidene group, a diphenylmethylene group, a dimethylsilylene group or a diphenylsilylene group; Each independently represents an unsubstituted or substituted cyclopentadienyl, fluorenyl or indenyl; M is a Group IVB metal; each X is independently selected from halogen, C1-C6 alkyl or C2-C6 alkenyl, In formula (II), Each independently represents a cyclopentadienyl, fluorenyl or indenyl group, R" and R"' are each independently selected from hydrogen, C1-C8 straight chain or branched alkyl, preferably hydrogen, C1-C4 straight chain or branched alkyl; M is a Group IVB metal; each X is independently selected from halogen, C1-C6 alkyl or C2-C6 alkenyl; (2) Catalyst B is at least one selected from the group consisting of metal complexes represented by general formula (IIIa) or (IIIb): In formula (IIIa) and (IIIb), R1 and R2 are independently hydrogen, C1-C4 alkyl, C1-C4 haloalkyl, halogen or C1-C4 alkoxy; R3, R4, R6 and R7 are independently C1-C6 alkyl, C3-C6 cycloalkyl, unsubstituted or substituted phenyl or phenyl-substituted C1-C4 alkyl; R5 and R8 are independently hydrogen, C1-C6 alkyl, C3-C6 cycloalkyl, unsubstituted or substituted phenyl, phenyl-substituted C1-C4 alkyl, halogen or C1-C4 alkoxy; M is nickel or palladium; X is halogen, wherein the substituted phenyl has 1 to 5 substituents selected from the group consisting of halogen, C1-C4 alkyl and C1-C4 haloalkyl, and (3) A co-catalyst selected from one or more of alkyl aluminum, alkyl aluminoxane and alkyl aluminum halide.
2. The catalyst system according to claim 1, wherein In formula (I) and formula (II), M is titanium, zirconium or hafnium, and X is halogen.
3. The catalyst system according to claim 1 or 2, wherein The catalyst B is selected from at least one of the following metal complexes:
4. The catalyst system according to any one of claims 1 to 3, wherein: The general structural formula of the co-catalyst alkyl aluminum is shown in formula (IVa), Al(R)3(IVa) wherein each group R is independently selected from C1-C8 alkyl, preferably selected from methyl, ethyl, propyl, butyl and isobutyl, most preferably selected from ethyl and isobutyl; The general structural formula of the co-catalyst alkylaluminoxane is as shown in formula (IVb) or (IVc), wherein each group R is independently selected from C1-C8 alkyl, preferably selected from methyl, ethyl, propyl, butyl and isobutyl, most preferably selected from methyl and ethyl, and n is any integer in the range of 1-50, preferably any integer in the range of 10-30; The general structural formula of the co-catalyst halogenated alkylaluminum is shown in Formula (IVd), To(R) n X 3-n (IVd) Wherein, each group R is independently selected from C1-C8 alkyl, preferably selected from methyl, ethyl, propyl, butyl and isobutyl, most preferably selected from ethyl and isobutyl, X is halogen, preferably chlorine or bromine, and n is 1 or 2.
5. The catalyst system according to any one of claims 1 to 4, wherein The molar ratio of the catalyst A to the catalyst B, calculated on the basis of the central metal atom, is 1:10 to 10:1, preferably 2:8 to 8:2, and more preferably 4:6 to 6:
4.
6. The catalyst system according to any one of claims 1 to 5, wherein The molar ratio of the total amount of the co-catalyst, calculated as aluminum atoms, to the total amount of the catalyst A and the catalyst B, calculated as central metal atoms, is (10-5000):1, preferably (100-2000):1, and more preferably (500-1000):
1.
7. A method for olefin polymerization, comprising contacting ethylene monomer, and optionally C3-C10 α-olefin, with the catalyst system according to any one of claims 1 to 6 in an organic solvent for polymerization reaction.
8. The method according to claim 7, wherein the organic solvent is selected from aromatic hydrocarbons, alkanes and halogenated alkanes, preferably selected from one or more of toluene, dichloromethane, n-pentane, cyclopentane, n-hexane, cyclohexane, n-heptane, n-octane and Isopare series solvents, more preferably selected from one or more of n-hexane, cyclohexane and toluene.
9. The method according to any one of claims 7-8, wherein the conditions of the polymerization reaction include: The temperature is 0-150°C, preferably 60-100°C; the polymerization pressure is 0.1-4.0Mpa, preferably 0.5-3.0Mpa.
Citation Information
Patent Citations
Asymmetric alpha-diimine nickel catalysts as well as preparation method and application thereof
CN110590980A
Catalyst composition applied to olefin polymerization and olefin polymerization method
CN108864337A
Catalyst composition and olefin polymerization method
CN108864340A
Composite catalyst and application thereof
CN114853947A
Cycloolefin block copolymer and preparation method thereof
CN114853964A